The lost world eaudiobook - Crichton, Michael (Jurassic Park, 2006)
"HARROWING THRILLS . . . FAST-PACED AND ENGAGING." —People It is now six years since the secret disaster at Jurassic Park, six years since the extraordinary dream of science and imagination came to a crashing end—the dinosaurs destroyed, the park dismantled, the island indefinitely closed to the public. There are rumors that something has survived. . . . "ACTION-PACKED." —New York Daily News "FAST AND GRIPPING." —The Washington Post Book World "A VERY SCARY READ." —Entertainment Weekly "AN EDGE-OF-THE-SEAT TALE." —St. Petersburg Times